Scientific support for gaining winning edge in Olympics: Nutrition perspective - Kalpana, K. (Journal of Physical Education & Sports Science, 2020)
Olympic sports cover a wide variety of sports than any other major international competitions. India has the scope of winning medals in Hockey, Archery, Shooting, Gymnastics, Weightlifting, Wrestling, Boxing, Tennis, Table Tennis, Badminton, and Athletics in the forthcoming Tokyo Olympics, 2020. In major international competitions, many of our athletes are losing the winning edge by a narrow margin. If concerted efforts are made by proper training and coaching, and continuous support of sports science and medicine, gaining the winning edge probably becomes easy in these sports.